(untitled) (Szociológiai Szemle, 2024)
The paper surveys a period of theories in quest of the occupational aggregate called white collar in the social structure. The disputes on the social structure were dominated by neo-Marxian and neo-Weberian objectives from the 60s to the early 80s (this theoretical field is called „Marx-Weber field of power” by the author). At first the paper presents and compares the positions of outlook represented by Karl Marx and Max Weber, then analyses the neo-Weberian and the neo-Marxian output of the period (Lockwood, Goldthorpe, Giddens and Parkin on the one hand, and Westergaard, Mallet, Poulantzas, Carchedi and Wright on the other). The „white-collar phenomenon” has got into a new context from the 80s onwards, which is partly indicated by the new theoretical points of view of French sociology (Bourdieu, Boltanski), and partly by German sociology moving away from theoretical abstraction (Kocka). According to the author so far not a single experiment has been able to offer a convincing answer to the basic question: how do we reach structural groups when starting from occupational categories.